Executive Compensation and Macroeconomic Fluctuations - Lars Oxelheim; Clas Wihlborg; Jianhoa Zhang (Research Institute of Industrial Economics (IFN), 2008)
Macroeconomic fluctuations affect corporations performance through demand and cost conditions. Incentive effects of performance-based compensation schemes for management may be weakened or biased by macroeconomic influences if management is unable to forecast macroeconomic fluctuations or unable to adjust operations in response to changes in macroeconomic conditions. In this paper we analyze the impact of macroeconomic, industry and firm-specific factors on salaries and bonus of CEOs in 131 Swedish corporations during the period 20012006. A distinction is made between anticipated and unanticipated macroeconomic fluctuations. The macroeconomic influences on performance and compensation can be expected to vary from firm to firm in terms of magnitude of effects, as well as in terms of relevant macroeconomic variables. The estimates obtained in this paper refer to the average impact across the sample of firms. We find that the average Swedish CEOs compensation is explained to a substantial extent by macroeconomic factors; less so by unanticipated factors alone.
Keywords: L14; L16; M14; M21; M52; 330; Executive Compensation; Macroeconomic Factors; Cash Compensation; Führungskräfte; Vergütungssystem; Konjunktur; Schweden